Implementasi Manajemen Pembelajaran Dalam Peningkatan Prestasi Belajar Siswa Sma Al Falakhussa’adah Way Kanan Di Masa Covid 19 - Muhammad Komarudin; Rita Linda; Tamyis (UNISAN JURNAL, 2022)
Learning management is very important in its position in order to improve the effectiveness of the teaching and learning process, especially during the emergency spread of the Corona Virus Disease-19 (COVID-19) as we are currently experiencing. Various efforts were made to improve the quality of education while still taking into account the health protocols in accordance with the Ministerial Decree 4. Various obstacles, difficulties, and limitations are faced in the teaching and learning process, ranging from factors of students, students’ families, as well as facilities and infrastructure that are less representative, but the Ministry of Education and Culture (Kemendikbud) continues to instruct all educators at all levels of education in order to create fun learning from home both students and college students. Therefore, the teacher’s role is very much needed in managing or managing learning starting from planning (planning), organizing (organizing), implementing (actuating) and evaluating (evaluating) in order to increase the effectiveness of the teaching and learning process during the current COVID-19 pandemic, both the implementation of distance learning in the network (online) and outside the network (offline).